Freire's Problem Posing Concept of Education: A Model for Nigeria System of Education - Nwobodo, Ratzinger E. E. (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
Education is across the globe, rightly considered a veritable tool for a holistic transformative development of both individuals and nations of the world. It is in this line that Fafunwa, an erudite scholar, described education as